Mastering Go programming - Andrawos, Mina (Packt Publishing, 2017)
"Go has moved from the state of tentative to mass adoption. Its C-like speed, simplicity, and power for a growing number of systems level programming domains make it an attractive option for programmers working with older cumbersome, statically typed languages. Golang has entered the space as an entirely viable language for accomplishing a huge array of low level programming and service infrastructure tasks. This video course not only gives you a deep insight into the fundamental mechanics behind the language, but also covers extensive practical topics on Go for modern software architectures. It shows you how to write Go in an intelligent, idiomatic way. After a brief re-acquaintance with the key building blocks of Go, we will also explore how we can build upon the unique capabilities of the language to write effective, powerful code you can employ to develop software. We look at packages, object-oriented programming, concurrency and reflection among other things. Moreover, you will learn about Go’s awesome built-in testing support feature. Along the way, build your skills in File handling techniques, Go packages for databases, data serialization approaches, message communications between Go services, and Go web applications. Get your hands on with a plenty of illustrative code samples, exercises and real-world scenarios that will help you build your own application. By the end of this course, you will be taught how to put this enhanced knowledge to build a real-world Spaceship application all by yourself with amazing features."--Resource description page.